ANALISIS PERLAKUAN AKUNTANSI ATAS AKUISISI OLEH PT. JHONSON & JHONSON TERHADAP PT. PFIZER DAN PENGARUHNYA TERHADAP KINERJA KEUANGAN - Wico Jontarudi Tarigan; Vitryani Tarigan; Djuli Sjafei Purba (UNHI Press, 2021)
This study is about the accounting treatment of acquisitions and their impact on the company's financial performance. The purpose of this research is to look at the proper implementation of the acquisition as stipulated by the relevant statutory arrangements, accounting treatment according to accounting standards, and its impact on the financial performance of the acquiring company. The research technique used is a descriptive research method to obtain a systematic, actual, and accurate description of the accounting treatment in accordance with the validity and accounting principles in analyzing acquisition transactions carried out by the company. Also, this method can collect and examine fiscal statement information identified with acquisitions to survey company presentations. From the analysis and discussion, it is suspected that the implementation of the acquisition transaction has complied with the laws and regulations, and guidelines provided by the public authorities. Accounting treatment for procurement in accordance with accounting standards. However, based on the author's analysis, the acquisition of the parent company does not have any adverse consequences, especially a decrease in performance. This can be seen from the increase in the solvency ratio and the decrease in the ratio of activity and profitability from the year after the acquisition. The company has a very large liability in foreign currency and has to bear a very large interest expense